Koperasi Sukses Indonesia - Muhammad Dawam Rahardjo (Universitas Proklamasi 45 Yogyakarta, 2011)
In June 2011 the PIP (Pusat Informasi Perkoperasian) magazine has been launched in releasing a list of 100 Successful Cooperative Indonesia. It has been following the tradition of the ICA Global 300 which contains a list of the most successful cooperatives from all over the world. We notice that a lot of cooperatives could be successful, however, we also are haunted by the question: “Are the successful cooperatives still have been known as ‘identity’ Coop?!” Did the cooperative have to abandon his identity in order to scoop up a successful?! This paper attemps to outline the dilemma.